Światotwórcze funkcje rekwizytu. Collectibles w dylogii „The Last of Us” jako źródło wiedzy o przeszłości - Pigulak, Joanna; Pigulak, Marcin (Przestrzenie Teorii, 2023)
The article concerns the functioning of selected collectibles in the post-apocalyptic dilogy of digital games The Last of Us (Naughty Dog, 2013–2020). The authors make a typology of collectibles and distinguish among them props that support the gameplay, characterize the characters and extend the storyworld, referring to the prop theory proposed by Kendal Walton. They are particularly interested in the last type of props, which include notes, diaries and letters left in various places of the world presented by anonymous members of the American community. The authors indicate that these props can be treated as specific artifacts of the past, which, although not important from the gameplay perspective, perform important world-creating functions. In this context, they describe collectibles as an element of historical culture (J. Rüsen) and a source of social memory (M. Golka), and discuss their allotopic potential (U. Eco, K.M. Maj). They refer to those props that shape the history and mythology of the post-apocalyptic world, and especially to the notes describing Outbreak Day, the apogee of the pandemic disease that decimated humanity in the game. Written sources are of a personal nature – they present an individual perspective on a breakthrough moment in the history of the depicted world. For this reason, the authors refer to them as ego-props, thus extending the concept of ego-document.